Capturing the complexity of workplace knowledge – a case study of recognition of prior learning in an automated production environment - Tennison, Colette (School of Education, 2025)
Braverman (1974) and others argue that the automation of the workplace results in deskilling and a reduction in the knowledge requirements for occupations. Recognition of prior learning (RPL) aims to recognise candidates' prior knowledge and skills learned in non-formal and informal contexts, including the workplace. The concern is that if Braverman's thesis is correct, the RPL process might be certifying ‘push-button operators' who do not have the required underpinning knowledge and skills for the occupation. However, the knowledge that operators in an automated production environment draw on in their work may be more complex than what the literature around deskilling suggests. This is hinted at in studies and literature about workplace learning such as those by Billett (2000, 2006) and others. The purpose of this research was to identify the types of knowledge surfaced through an RPL programme conducted in an automated production environment in order to explore the nature of this workplace knowledge and to further develop a conceptual language for describing and analysing the knowledge present. This qualitative research project was based on a case study approach drawing on Participatory Action Research and Educational Design Research Methodology. It drew on an RPL programme conducted for machine operators on a high-speed beverage packaging line and focused on the knowledge surfaced by the tools used to assess the candidates during the RPL programme. The analysis in this thesis draws on Gamble's (2016) study of work which is based on the social realist tradition and provides a conceptual framework for examining knowledge present in work contexts. This is further expanded through Winch's (2012) conceptualisation of skill as well the literature on craft and tacit knowledge, together with Guile and Unwin's (2019) concept of expertise. In order to clearly understand the complexity of the knowledge surfaced in this case study, it was necessary to use various analytical lenses to ‘pull apart' the range of knowledge types and categories of knowledge present. The findings of this research point to the complexity of knowledge that is drawn upon by machine operators on an automated production line. This complexity highlights the depth of knowledge required to develop the expertise and professional judgement needed to function in the workplace. Having analysed the knowledge types present separately, they were drawn together in an attempt to create a more holistic picture of what constitutes workplace expertise. The concepts of craft-like and tacit knowledge, together with expertise, allowed for the development of a language of description to address the ‘discursive gap' (Ensor and Hoadley, 2004) between the analytical lens and the empirical data. This conceptualisation was further developed in the final chapter of the thesis as it provided insights into what a holistic picture of occupational expertise could look like in an automated production environment. The thesis concludes that the complexity of workplace knowledge surfaced through the RPL programme indicates that the RPL candidates were not just ‘push-button operators'. Theoretical conclusions drawn in the final chapter point to the contribution of the thesis in developing a more holistic conception of expertise that accounts for the complexity of workplace knowledge. The final chapter also points to the importance of RPL programmes that can surface forms of knowledge from a variety of contexts and reflects on the contributions of this research for RPL practice. Finally, the chapter offers suggestions for how considerations around the development of craft-like and tacit knowledge, as well as professional judgement, should be taken into account when developing vocational curricula.